Simulasi Model Sistem Dinamik Ketersediaan Bawang Putih (Allium sativum, L.) di Provinsi Bali - Ima Dudin, Muhammad Dika; Wiranatha, Agung Suryawan; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): Maret, 2020)
The demand of garlics in Bali is considerably high and exceed the capability of farmers in Bali to produce garlics. Therefore garlics were supplied from other islands of Indonesia. Demand of garlics will increase along with the increasing number of population and the number of foods industry. The aims of this research were to determine the factors that affect demand and supply garlic, to analyze the stock of garlics, and policy recommendations which can be implemented to provide sufficient garlics in Bali, therefore the price will remain stable. This research was conducted in Bali Province using a system dynamics modelling, with the length of simulation period from 2012 to 2024. The research results showed the factors that affected of garlic stock in Bali were the production of garlics, demand of garlics, inter island supply and price. Further, the simulation results showed that the production of garlics in Bali wasn’t able to fulfill the demand of garlics therefore it affected the price. So, it requires inter-island supply to stabilize price and to fulfill the demand of garlics. Based on some simulation scenarios, the most effective policy could be developed in order to minimize inter-island supply and stabilize prices is through increasing garlic planting area of 35%/year and increasing land productivity of garlic plantation of 5 ton/year. Keywords : system dynamics, availability of garlic, Bali Province.